2016
DOI: 10.21010/ajid.v10i2.6
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Brucellosis in Cattle and Their Handlers in North Tongu District of Volta Region, Ghana

Abstract: Background: Brucellosis is a zoonotic pathogen responsible for great economic losses in most sub-Saharan nations. Although Ghana has successfully implemented the "One Health" initiative for the control of some emerging infectious zoonotic diseases with pandemic potential like Avian Influenza, there is very limited data available on brucellosis especially human brucellosis prevalence. He objective of his study is to determine the seroprevalence of human and bovine brucellosis as well as the predisposing factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 14 publications
4
28
2
Order By: Relevance
“…Tasiame et al . () reported a prevalence of bovine Brucellosis of 23% in the North Tongu area. How much of the abortions occurring in the study area due to Q fever and/or in concomitant with other abortion causing infections is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tasiame et al . () reported a prevalence of bovine Brucellosis of 23% in the North Tongu area. How much of the abortions occurring in the study area due to Q fever and/or in concomitant with other abortion causing infections is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…An overall prevalence of 21% was (Kanout e et al 2017) was an indication that it could be widespread in Ghana, although not reported and surveilled. According to Tasiame et al (2016), about 80% of the livestock population in the Tongu districts were bred and the area served as a major source of breeding stock to other livestock farms in southern Ghana. The latter together with heavy flow of livestock through transhumance and commercial purposes into northern Ghana suggest that Q fever could be widespread in most livestock communities in Ghana.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations